The next generation Birmingham Solar Oscillations Network (BiSON) spectrophotometer: a new miniaturized instrument for helioseismology. Issue 1 (2nd November 2022) - Hale, S J; Chaplin, W J; Davies, G R; Elsworth, Y P; Howe, R
Abstract: We describe a new spectrophotometer for the Birmingham Solar Oscillations Network (BiSON), based on a next generation observation platform, BiSON:NG, a significantly miniaturized system making use of inexpensive consumer-grade hardware and off-the-shelf components, where possible. We show through system modelling and simulation, along with a summer observing campaign, that the prototype instrument produces data on the Sun's low-degree acoustic (p-mode) oscillations that are of equal quality and can be seamlessly integrated into the existing network. Refreshing the existing ageing hardware, and the extended observational network potential of BiSON:NG, will secure our ongoing programme of high-quality synoptic observations of the Sun's low-degree oscillations (e.g. for seismic monitoring of the solar cycle at a 'whole Sun' level).